Why referred potential heart donors aren't used. - Richards, P S (1993)
Heart donor demand far exceeds supply. We evaluated donor referrals to 1 organ procurement agency in an attempt to determine why many potential cardiac donors are not used. Of 430 referrals between September 1989 and August 1991, 169 hearts (39%) were harvested. In potential donors ultimately not yielding a heart, 38.7% were unavailable because the family refused to consent to organ donation, 36% were medically unsuitable, and 16.1% did not meet standard brain death criteria. Of the 94 donors not used for medical reasons, 43.6% had cardiac arrest, 17% had hypotension, 12.8% were drug abusers, 6.4% had sepsis, 5.3% had hepatitis, 5.3% had an acute myocardial infarction, 3.2% had low ejection fraction levels, and 2.1% tested positive for human immunodeficiency virus or syphilis (4.3% were not specified). A significant difference (p = 0.001) in racial distribution surfaced; Blacks and Hispanics constituted 27.2% of the donor group but 46.3% of the non-donor group. These data confirm that strategies must be created to continue educating the public and physicians in order to increase consent rates, optimize donor selection, and improve physician awareness of brain death criteria.